(untitled) (La Rivada, 2024)
The present work addresses the fantasy genre and its relationship with myth, understanding both narratives as cultural frameworks and as fields for constructing meaning. It aims to establish certain regularities that allow an approach to the ways in which narrative worlds are configured. The essay traces the origins of the genre, where myth emerges as one of its main roots and then delves into the tensions around the definition of fantasy and its association with the unreal and the extraordinary. Thus, the notion of world becomes central, particularly in relation to the significance of spatial-temporal coordinates, and how transcendence is represented in establishing the continuities and differences between fantasy and myth. Along this journey, the affective dimension and the creative tension between the mimetic and symbolic drive in both narrative forms gain importance.